The Recording of Student Performance in the Microbiology Laboratory as a Training, Tutorial, and Motivational Tool - Steven M. Lipson; Marina Gair (Journal of Microbiology & Biology Education, 2011)
The laboratory component of a microbiology course consists of exercises which mandate a level of proficiency and manual dexterity equal to and often beyond that recognized among other biology courses. Bacterial growth, maintenance, identification (e.g., Gram stain, biochemical tests, genomics), as well as the continuous need to maintain laboratory safety and sterile technique, are only a few skills/responsibilities critical to the discipline of microbiology. Performance of the Gram stain remains one of the most basic and pivotal skills that must be mastered in the microbiology laboratory. However, a number of students continually have difficulty executing the Gram stain and preparative procedures associated with the test. In order to address this issue, we incorporated real-time digital recording as a supplemental teaching aid in the microbiology laboratory. Our use of the digital movie camera in the teaching setting served to enhance interest, motivate students, and in general, improve student performance.